Pengaruh Pengembangan Karir, Motivasi Kerja dan Pemberian Kompensasi terhadap Loyalitas Kerja Karyawan (Studi Kasus pada Karyawan PT. Tribun Berita Online) - Vivilia Aninditya Vrisna Willy Rizky Utami; Christantius Dwiatmadja (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of career development variables, work motivation and compensation in PT. Tribun Berita Online partial and simultant on the level of employee loyalty. This research has three hypotheses tested that will be explained, where the three hypotheses will be explained partial tested. This study uses a statistical analysis using the IBM SPSS Statistics Application 23. The data of the research respondents were obtained as many as 62 respondents using the characteristics of regular employee with more than 2 years (> 2 years). The results of this study simultant there is an influence between career development, work motivation and compensation for employee loyalty at PT. Tribun Berita Online. However, only partial tested career development variables have a positive effect on employee work loyalty, but work motivation and compensation don’t have a partial tested effect on work loyalty.